THEORY OF MUSICAL TEXTURE IN RUSSIA: MODERN ASPECTS OF STUDYING - V. Titova, Elena (Revista Inclusiones, 2021)
The main object of study in the article is the theory of texture, which developed in Russia in stages and has undergone a significant evolution. The origins of theoretical attitudes about texture go back to the era of the Russian avant-garde and can be traced in the theory of music, literature, and fine arts. In modern musicology, understanding the problems of musical texture is aimed at studying the processes of organization of sound tissue, systems of its formation, which reflect the attitudes of various styles and genres. This area of research of texture in music is determined by the terms futurology (definition Kholopov) or factorbeta (definition Sviridova). Theoretical ideas about musical texture are developed in such branches of musicology as harmony, polyphony, and analysis of musical works. The formation of the foundations of the theory of texture in musicology is associated with the names of leading Russian scientists Tyulin, Kholopov, Bershadskaya, Kholopova, and others. The development of the invoice theory goes in the following directions: development of new terminology that meets the new techniques of modern composition techniques and is able to perform modern analytical operations. In addition, there are also сentral categories in the area of issues under discussion, the meaning of which is subject to revision or clarification. In recent years, musical texture has become an area of methodological and practical development of musical and theoretical disciplines.